2014
DOI: 10.1007/s11605-013-2332-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Learning Curve and Predictors of Intraoperative Difficulty for Peroral Esophageal Myotomy (POEM)

Abstract: In this series, overall procedure time did not decrease with experience and may not be an important marker of procedural skill for POEM. Prior endoscopic treatment, longer symptom duration, and esophageal dilatation may result in increased operative difficulty during POEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 21 publications
2
85
1
Order By: Relevance
“…This is likely a result of the temporary relief these patients experienced following their previous treatments resulting in a relative delay in presentation prior to POEM. Lastly, POEM is an advanced endoscopic technique and requires careful repetition and training that may not be available to all practitioners, thus limiting reproducibility [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely a result of the temporary relief these patients experienced following their previous treatments resulting in a relative delay in presentation prior to POEM. Lastly, POEM is an advanced endoscopic technique and requires careful repetition and training that may not be available to all practitioners, thus limiting reproducibility [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…During subgroup analysis of patients with or without histories of endoscopic intervention, one group found no difference in procedure duration, intraoperative adverse events, or efficacy, 37 whereas the other group found prior endoscopic treatment to be a predictor of increased procedure time. 38 The discordant findings may be related to methodologic issues such as the very small numbers of previously treated patients included in these studies (4 and 12, respectively). POEM after failed surgical Heller myotomy is reported to be more challenging, but recent reports demonstrate excellent efficacy when POEM is performed by experienced operators.…”
Section: Per-oral Endoscopic Myotomy For Achalasia: the Historical Anmentioning
confidence: 94%
“…47 Another study about the learning curve of POEM also showed that previous endoscopic treatment was one of the independent predictive factors of a longer procedure time. 48 However, there were also several contrary results that showed no significant difference even in operation time, efficacy, and safety. [49][50][51] POEM could also be used in the setting of recurrence or failure after previous surgical myotomy.…”
Section: Previous Endoscopic and Surgical Treatmentmentioning
confidence: 98%